Polish Contemporary Migration: From Co‐migrants to Project ME. (19th April 2013) - Isański, Jakub; Mleczko, Agata; Eid, Renata Seredyńska‐Abou
Abstract International migration mirrors contemporary society in all its complexity. What has not changed for centuries is the principal motif: people leave their country of origin hoping for a better life. Poland has a long history of emigration: Poles have been migrating for more than 200 years for political, economic and social reasons. In recent decades, Polish migration patterns have undergone dramatic changes. Using online survey data, this article explores new trends in Polish migration since the country's accession to the European Union in 2004. The survey was focused on Polish migrants who stayed abroad for some time, those who stayed abroad before the accession, those who returned to Poland or those who experienced multiple travels and have an ongoing migration project. We conclude that new trends have emerged among Polish migrants. Contemporary migrants are aware of the benefits related to migration and are capable of implementing their migration project quite skilfully. Their high susceptibility to the economic setting proves their flexibility. Polish migrants highly value their new lifestyle abroad and consider friends their most important source of support.